Renewable Energy, Shocks and the Growth Agenda: A Dynamic Stochastic General Equilibrium Approach - Alege, Philip; Oye, Queen-Esther; Adu, Omobola (International Journal of Energy Economics and Policy, 2018)
Macroeconomic fluctuations observed in real economies are results of identifiable shocks in form of technology, monetary, fiscal, trade, energy or a combination of these shocks. The adverse effects of energy price shocks, in recent decades, have made the call for renewable energy source important. This call is most appropriate in a mono-cultural economy where the fluctuations in crude oil pricing are easily transmitted into the economy. Therefore, this paper seeks to investigate the consequences of technology, and energy shocks on key macroeconomic variables including output and consumption using an energy augmented Small Open Economy Dynamic Stochastic General Equilibrium (SOEDSGE) model. The model is estimated using Bayesian techniques under different scenarios in order to show the various ramifications of the shocks to the Nigerian economy. The findings show that shocks to the renewable energy sector have more impact of the Nigerian economy compared to shocks to the fossil fuel sector. Keywords: fossil fuels, technology shocks, demand shocks, renewable energy, SOEDSGE JEL Classifications: E32, K32, P18 DOI: https://doi.org/10.32479/ijeep.6953